Mobilnost in železniška podpora industriji - Murtič, Sašo (Perfectus AC, 2018)
Through the research we wanted to find out what is the mobility and system logistical connection of the railway with industrial production in the local area and how the railway with its capacity manages to meet the needs of industry for transport and other processes that enable transport. We aimed to find relevant equivalents that will show us on the basis of which synergies of business processes the railway is involved in industrial production and how the industry, taking into account its mobility and capacity, contributes to the overall development. Already from the organization of railway transport and connections with industry, companies and individuals, we obtained a number of data that explain mobility, the interconnection of railways with industry and industry with railways. From the data, we learned how the railway is mobile, agile and how it is integrated into the needs of the industry and its development. The results show us the economic calculations of the justification of the system connection, and the legal basis the normative admissibility. The data were obtained by inventorying the arrived railway compositions, the amount of cargo delivered and the permissible railway load. We obtained a lot of data from the railway manager of Slovenske železnice and industry in the region. We also obtained data through a direct connection with some organizations, companies and individuals involved in transport and related to industry and railways. Unfortunately, due to the scope of the research area, we limited ourselves to mobility and those data and transports that are directly intended for transport for the needs of industry and to those data that were given to us by the railway or industry in the region to protect business secrets.
Keywords: connectivity; industrija; industry; logistics; logistika; mobility; mobilnost; povezanost; railway; železnica